Anxiety and depression as risk factors for suicidal ideation in adolescentes - Castillo-Barriga, Francisco (2025)
Suicidal ideation in adolescents is a complex and multifactorial problem that has gained significant relevance in recent decades. Stigmatized as a critical stage, adolescence is a period in which emotions are more intense, as cognitive development is still in progress, making young people more vulnerable. It is considered by some as the most problematic phase, where high-risk issues, including suicidal ideation, emerge. For many, adolescence represents the healthiest period from a biological perspective, with its understanding being more of a cultural construct rather than solely a biological transition. Consequently, this study aimed to understand the factors influencing suicidal ideation in students from a Secondary Education Institution in the city of Juliaca, Peru. The research followed a cross-sectional design with a descriptive-explanatory approach. A total of 801 students from the first to the fifth year of secondary school participated in the study, all enrolled and actively attending their academic activities. The average age was 14.97 ± 1.92 years, with 423 being female (52.8%) and 378 male (47.2%). The research findings revealed significant results in three factors: anxiety (β = 0.395; P < 0.001), depression (β = 0.258; P < 0.01), and adolescents’ age (β = 0.101; P < 0.001). In this context, preventive interventions, emotional education, and family support are essential to mitigate the risk of suicide in adolescents.